Pengaruh CAR, NPL, dan LDR terhadap Profitabilitas (Studi Empiris pada Perbankan yang Terdaftar di Bursa Efek Indonesia Selama Periode 2016-2018) - Syirin Humairoh; Rachma Agustina (JFAS : Journal of Finance and Accounting Studies, 2022)
Profitability is the ratio which links the profit from sales and investment. From the profitability ratio,the stakeholder and shareholder can see and understand the level of company profitability. This study has purpose to determine the effect of Capital Adequacy Ratio / CAR, Loan To Deposit Ratio / LDR, Non Performing Loans / NPL towards banking companies listed on the Indonesian stock exchange with time period of 2016-2018. In this research, researchers used sampling method which is a purposive sampling method. Samples that meet the criteria in this study are 16 banks for the time period of 2016-2018. The type of research used in this study is quantitative research. The results of this study indicate that the Capital Adequacy Ratio / CAR has a significant effect on profitability, Non Performing Loans / NPL do not have a significant effect on profitability, while the Loan To Deposit Ratio / LDR has no significant effect on profitability.  Keywords: CAR; NPL; LDR; Profitability